Portal Vein Thrombosis: Introduction to Imaging and Etiology - Gueyikian, Sebouh; Ferral, Hector (Seminars in Interventional Radiology, 2023)
Portal vein thrombosis (PVT) is a complex medical condition that presents differently depending on the etiology. Appropriate imaging is necessary to determine the extent of clot, as well as its chronicity. While determining the characteristics of the PVT, imaging may also reveal the underlying cause of PVT. The purpose of this article is to describe the most common imaging modalities used in the evaluation of PVT, and to describe the findings of PVT.
Keywords: portal vein thrombus; imaging; etiologies; transjugular intrahepatic portosystemic shunt; interventional radiology